Perfil epidemiológico dos pacientes atendidos em programa de acompanhamento e tratamento da osteoartrite do joelho: estudo observacional e transversal - Araújo de Paula Santos, Pedro Felipe; Pereira da Silva, Vitor; Valente Maia, Phelippe Augusto; de Paula Mozella, Alan; Chagas Macedo Pinheiro , Marcia Cristina; Tie Minamoto, Sandra; Branco de Sousa, Eduardo (Clinical and Biomedical Research, 2024)
Introduction: Osteoarthritis (OA) is the main cause of decreased joint function, with an impact on activities of daily living. The objective of the study was to evaluate the epidemiological profile of patients treated at an outpatient clinic for conservative treatment of knee osteoarthritis in a tertiary-level institution of the Unified Health System. Methods: An observational and cross-sectional study was carried out evaluating 577 patients with knee osteoarthritis undergoing pharmacological treatment, from September 2014 to April 2019. The following epidemiological data were collected: sex; date of birth; weight and height; laterality; OA severity, according to the Ahlback classification, modified by Keyes and Goodfellow; presence of joint crepitus and axis deviation of the lower limbs. Results: No difference was observed between the groups in relation to OA severity (p = 0.75), gender (p=0.90), presence of joint crepitus (p=0.57), laterality (p=0. 89), axis deviation of the lower limbs (p=0.75), nor history of previous treatments (p=0.46). Conclusion: The population profile of patients with knee osteoarthritis undergoing conservative treatment is mostly female, obese and over 60 years old. Ahlback grades II and III are preponderant.